Hormesis at the National Toxicology Program (NTP): Evidence of Hormetic Dose Responses in NTP Dose-Range Studies - Edward J. Calabrese; Linda A. Baldwin (Dose-Response, 2003)
The National Toxicology Program (NTP) dose-ranging studies typically employ five dosages and a concurrent control and are conducted for 2- and 13-week exposure periods. Because five doses are employed it suggested the possibilities of the occurrence of sub-NOAEL doses in many of these bioassays and of evaluating the occurrence of hormesis within the NTP bioassay. As a result, 59 environmentally relevant agents in the NTP toxicity database were assessed for their capacity to affect hormetic dose responses for growth as measured by change in weight gain. Hormetic effects were observed with 51 (88%) of the 58 agents evaluated. When considered by species, hormetic effects were observed in 48% (98/205) of bioassays involving mice and 14% (29/204) of bioassays involving rats. Hormetic effects were seen in a comparable fashion between males and females of both mice (i.e., 47 male and 51 female) and rats (13 male and 16 female rats). These observations represent a new finding within the NTP bioassay database that have potential implications for issues relating to study design and endpoint measured, as well as underlying biological mechanisms that affect efficiency of nutrient utilization under conditions of low-level toxicant exposure.